A commentary on "First-hand experience of accessible information". Issue 2 (7th April 2015) - Buell, Susan
Abstract : Purpose: – The purpose of this paper is to provide a commentary on Mander's paper on people with learning disabilities' first-hand experience of accessible information. Design/methodology/approach: – The commentary reflects on some of the findings presented by Mander and builds on these, with particular emphasis on what it means to understand information. Findings: – Everything from initial product design to building capacity and constructing knowledge requires expertise and attention to detail. Originality/value: – There are no easy fix solutions to achieving understanding of information for people who have learning disabilities.